Computational dosimetry in MRI in presence of hip, knee or shoulder implants: do we need accurate surgery models?. (21st December 2022) - Arduino, Alessandro; Baruffaldi, Fabio; Bottauscio, Oriano; Chiampi, Mario; Martinez, Jessica A; Zanovello, Umberto; Zilberti, Luca
Abstract: Objective. To quantify the effects of different levels of realism in the description of the anatomy around hip, knee or shoulder implants when simulating, numerically, radiofrequency and gradient-induced heating in magnetic resonance imaging. This quantification is needed to define how precise the digital human model modified with the implant should be to get realistic dosimetric assessments. Approach . The analysis is based on a large number of numerical simulations where four 'levels of realism' have been adopted in modelling human bodies carrying orthopaedic implants. Main results . Results show that the quantification of the heating due to switched gradient fields does not strictly require a detailed local anatomical description when preparing the digital human model carrying an implant. In this case, a simple overlapping of the implant CAD with the body anatomy is sufficient to provide a quite good and conservative estimation of the heating. On the contrary, the evaluation of the electromagnetic field distribution and heating caused by the radiofrequency field requires an accurate description of the tissues around the prosthesis. Significance . The results of this paper provide hints for selecting the 'level of realism' in the definition of the anatomical models with embedded passive implants when performing simulations that should reproduce, as closely as possible, the in vivo scenarios of patients carrying orthopaedic implants.